Deteksi Dini Hipertensi Dan Edukasi Gizi Sebagai Upaya Meningkatkan Kualitas Hidup Lansia Di Dusun 3 Pekon Tulung Agung - Masayu Dian Khairani; Nurul Utami; Mutia Cahya Kinanti; Delia Amanda; Eka Aprilia Sari (Journal of Innovative and Creativity (Joecy), 2026)
Hypertension is one of the most common health problems among older adults and has the potential to cause serious complications if not detected and managed appropriately. Hamlet 3 of Tulung Agung Village has a relatively high number of elderly individuals with hypertension, accompanied by low public awareness regarding routine blood pressure monitoring and the implementation of healthy lifestyle practices. This community service program aimed to improve the knowledge and awareness of older adults regarding the early detection of hypertension and its non-pharmacological management. The implementation methods included community outreach and health problem identification, health education, blood pressure screening, nutrition education based on the Dietary Approaches to Stop Hypertension (DASH) diet, and evaluation through pre-tests and post-tests. The program was conducted on January 19, 2026, involving 34 older adults in Hamlet 3 of Tulung Agung Village. The results showed the identification of hypertension and pre-hypertension cases through blood pressure screening and an increase in participants' knowledge regarding the concept of hypertension, risk factors, and management strategies through dietary modifications and healthy lifestyle practices. The support of community health volunteers and the active participation of the elderly participants were the main contributing factors to the success of the program. This program is expected to strengthen hypertension control efforts and serve as a foundation for the sustainable development of elderly health programs at the village level.